Psychological Stress and Life Satisfaction among Parents of Children with Autistic Spectrum Disorder - H. AL-Hadrawi, Hayder; K. Faid, Acklas (International Journal of Psychosocial Rehabilitation, 2020)
Background: Parents of children with different disabilities have been found as a vulnerable group for significant levels of psychological stress; however, the stress is higher among parents caring for children with autism. Parents’ stress negatively impacts children in many ways; it influences the cognitive function of children, in addition to their behavior and the communication skills. Aims: This study aimed to measure the level of psychological stress among parents of children with autistic spectrum disorder, as well as measuring the relationship between parenting stress and their life satisfaction. Method: A descriptive correlational study was conducted on a convenience sample (N = 75) of parents of autistic children. The Arabic Version of Cohen’s Perceived Stress Scale and the Satisfaction with Life Scale were used to assess the level of stress and the level of life satisfaction among parents of children with autistic spectrum disorder (ASD) Results: About 83% of parents have levels of psychological stress ranged between moderate to severe level and 36% of parents were dissatisfied with their lives. There was an inverse correlation between parents’ psychological stress and their satisfaction with life . Conclusion and recommendations: Having a child with autism is extremely stressful as a result of the total dependency on families in all children’s daily life activities. Parents’ satisfaction level with life is linked to their level of psychological stress; consequently, parents’ stress can be an alarming sign against parents’ future health and lives, which increases the need for significant attention in terms of stress management programs designed for parents and new strategies of making autistic children as self-dependent as possible.